Application, emerging health benefits, and dosage effects of blackcurrant food formats. (August 2022) - Xue, Bin; Hui, Xiaodan; Chen, Xinyi; Luo, Shuangyan; Dilrukshi, H.N.N.; Wu, Gang; Chen, Chunbo
Graphical abstract: Highlights: Encapsulation strategies are effective and protective for BC phytochemicals. BC pomace is a natural vehicle to deliver BC bioactive components. BC powder is a natural vehicle to deliver BC bioactive components. Application of BC derivatives into food products needs to be studied separately. Abstract: Blackcurrant is rich in polyphenols, especially anthocyanins, and is regarded as an healthy food due to its various potential health benefits. The objectives of this review were to introduce five common types of blackcurrant food formats (blackcurrant juice concentrate/extract/powder/pomace/encapsulates) to summarize their practical applications in some real food matrices to produce blackcurrant containing functional food products. The emerging health benefits of these blackcurrant food formats that have been reported in the last three years were also clarified. Furthermore, the importance of their dose-dependent effects in practical applications was underlined. Encapsulation strategies are effective and protective manners to deliver blackcurrant concentrate or extract to various food matrices by the formation of encapsulates. Blackcurrant powder and blackcurrant pomace are natural vehicles for the delivery of blackcurrant bioactive components. Additionally, the dose-dependent effectiveness of these blackcurrant food formats towards various diseases needs to be investigated separately.